PENGARUH PENDEKATAN KONSTRUKTIVISTIK TERHADAP PEROLEHAN BELAJAR TEMATIK PESERTA DIDIK KELAS IV SEKOLAH DASAR - Fitriadi, Muhammad; Marzuki, Marzuki; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to investigate the effect of constructivist approach on thematic learning achievement of 4th grade students of Public Elementary School 03 Pontianak Selatan. This study uses an experimental method with pre-experimental design and type of one-group pretest-posttest design. The population of this research was all of 4th grade students ofPublic Elementary School 03 Pontianak Selatan. The sampling technique uses non probability sampling with purposive sampling type and the sample are 4thB grade students totaling 36 students. Data collection techniques use measurement techniques in the form of multiple choice test. Based on data analysis result, average of pretest and posttest score were 65,08 and 77,83. Result of t-test obtained tcount = 8,098 and ttable (Î± = 5%; dk = 35) = 2,03. Because tcount > ttable, its mean H0 rejected and Ha accepted. The effect size result was 0,77 with medium criteria. The conclusion, that constructivist approach gives effect to thematic learning achievement of 4th grade students of Pontianak Selatan 03 Public Elementary School with medium criteria.Â Keyword : The Effect, Constructivist Approach, Learning Achievement, Thematic Learning